(untitled) (American Journal of Islam and Society, 1992)
Consideration of ‘Urf by the Khulafla’ al Rashidun ‘Urf (custom) and ‘adah (tradition) are very ancient and important somes of Islamic law. As the pre-Islamic Arabs had no written documents or script, their social systems were regulated by custom and tradition. According to the available historical accounts, the khulafa’ al rashidun retained many pre-Islamic social customs and traditions and also adopted and established some useful nonindigenous customs. Such borrowing was quite acceptable in their eyes, for the Prophet himself had acknowledged the validity of some pre-Islamic customs that were compatible with the letter and spirit of the revelation. At the time of the Prophet, the Arabian peninsula was the home of many different customs and traditions. The Arabs were mainly idol worshippets, and this outlook was reflected in their customs. However, they had also retained a pottion of the legacy of Ibrahim: ceremonies related to the Ka‘bah and circumcision. These ceremonies provided the basis for the establishment of social traditions. Many pre-Islamic customs were still practiced during the period of the khulafa’ al rashidun. For instance, grain (i.e., wheat, barley) continued to be regarded as kayli (measured by capacity) and gold and silver were considered wazni (me asured by weight). The same custom and usage were followed in commercial transactions made by the Prophet and his four immediate successors. The fuqaha’ later based many of the rules concerning zakah (poor due), sadaqah (charity), and kaffarah (expiation) ...